Cold-inducible RNA-binding protein mediates airway inflammation and mucus hypersecretion through a post-transcriptional regulatory mechanism under cold stress - Juan, Yang; Haiqiao, Wu; Xie, Wenyao; Huaping, Huang; Zhong, Han; Xiangdong, Zhou; Kolosov, Victor P.; Perelman, Juliy M. (The international journal of biochemistry & cell biology, 2016)
Acute or chronic cold exposure exacerbates chronic inflammatory airway diseases, such as chronic obstructive pulmonary disease (COPD) and asthma. Cold-inducible RNA-binding protein (CIRP) is a cold-shock protein and is induced by various environmental stressors, such as hypothermia and hypoxia. In this study, we showed that CIRP gene and protein levels were significantly increased in patients with COPD and in rats with chronic airway inflammation compared with healthy subjects. Similarly, inflammatory cytokine production and MUC5AC secretion were up-regulated in rats following cigarette smoke inhalation. Cold temperature-induced CIRP overexpression and translocation were shown to be dependent on arginine methylation in vitro. CIRP overexpression promoted stress granule (SG) assembly. In the cytoplasm, the stability of pro-inflammatory cytokine mRNAs was increased through specific interactions between CIRP and mediator mRNA 3⿲-UTRs; these interactions increased the mRNA translation, resulting in MUC5AC overproduction in response to cold stress. Conversely, CIRP silencing and a methyltransferase inhibitor (adenosine dialdehyde) promoted cytokine mRNA degradation and inhibited the inflammatory response and mucus hypersecretion. These findings indicate that cold temperature can induce an airway inflammatory response and excess mucus production via a CIRP-mediated increase in mRNA stability and protein translation.